Leibniz's critique of Descartes' theory of Qualia - Teixeira, William (Sofia, 2025)
This paper aims at trying to answer Leibniz’s critique of Descartes’ theory of qualia. First, I discuss the main reason given by Leibniz for assigning qualia to the Cartesian theory of perception. Then, I put forward the reasons why I believe that it is possible to reject Leibniz’s critique. In my view, there are three elements found in Descartes’ philosophy which should be considered in order to answer Leibniz’s critique: the institution of nature, the deist occasionalism and the psychophysical parallelism. I conclude by suggesting that all these three elements of Descartes’ philosophy seem to have exerted a great influence in shaping both Leibniz’s hypothesis of pre-established harmony and his expressive theory of perception, which were the alternatives that the German philosopher had conceived in order to solve the qualia problem.
Keywords: Qualia; institution of nature; occasionalism; psychophysical parallelism; pre-established harmony; expression